A transparent, stretchable, stable, self-adhesive ionogel-based strain sensor for human motion monitoring. Issue 36 (4th September 2019) - Sun, Jingxian; Yuan, Yixin; Lu, Guoqiang; Li, Lingfeng; Zhu, Xiaoqun; Nie, Jun
Abstract : A multi-functional ionogel-based strain sensor was synthesized to detect various human motions. Abstract : It has been a challenge to integrate multifunctionalities, such as transparency, stretchability, stability, and adhesiveness, in a single strain sensor. In this study, a novel ionogel was synthesized by the photopolymerization of butyl acrylate (BA) in the ionic liquid bis(trifluoromethylsulfonyl imide) ([BMIM]TFSI). Due to good compatibility between BA and [BMIM]TFSI, the achieved ionogel had excellent transparency and high stretchability. Attributed to the hydrophobicity of BA and [BMIM]TFSI and high boiling point of [BMIM]TFSI, the ionogel exhibited super environmental stability; in other words, there was no weight change in the ambient environment. Moreover, the ionogel could repetitively adhere to different substrates firmly even under water. Due to its excellent electromechanical properties such as fast response speed, low electrical hysteresis, high sensitivity and good repeatability, the ionogel strain sensor could detect various human motions including the bending of a finger, elbow, wrist and the beating of the human pulse. In addition, the sensor exhibited good sensitivity in temperature sensing. Therefore, this ionogel has a promising application in artificial flexible electronics.